Manganese removal from groundwater by oxide-carbonate manganese ore - Mamchencko, Aleksei; Savchenko, Olga; Chernova, Nataliia; Yakupova, Irina (My University, 2012)
Most of underground water sources in Ukraine contain increased concentration of manganese. Modified natural oxide-carbonate manganese ore (OCMO-Mn) was obtained. The main technological parameters of manganese removal from water onto filtration medium, average rate of filtration and backwashing frequency was studied.
Keywords: manganese; underground water; well; iron removal; OCMO-Mn; кафедра технології цукру і підготовки води